10=-3F+10N

Simple and best practice solution for 10=-3F+10N equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=-3F+10N equation:


Simplifying
10 = -3F + 10N

Solving
10 = -3F + 10N

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Add '3F' to each side of the equation.
10 + 3F = -3F + 3F + 10N

Combine like terms: -3F + 3F = 0
10 + 3F = 0 + 10N
10 + 3F = 10N

Add '-10' to each side of the equation.
10 + -10 + 3F = -10 + 10N

Combine like terms: 10 + -10 = 0
0 + 3F = -10 + 10N
3F = -10 + 10N

Divide each side by '3'.
F = -3.333333333 + 3.333333333N

Simplifying
F = -3.333333333 + 3.333333333N

See similar equations:

| (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 | | y=x^2+12+35 | | 5-3x=4x+12 | | 6-3A+5B=0 | | (-9x+11)8= | | 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 | | 9=-2x+4 | | 7(p+1)=p-9 | | C=3.14(5) | | -5/6f+1=-4 | | 12-2A-2B=0 | | 5+-26=18x | | 2=15x | | (x+8)(x-3)+30=0 | | 52=4x-4 | | -4/6f+1=-4 | | 7u+9u+u=140 | | 7y-2=13+10 | | 4z-2=2+7 |

Equations solver categories